Technical Knowledge (ITK) in capture fisheries: A case study in Vypeen island of Ernakulam district. - Shyam S. Salim and Pearly Antony O. Indigenous (Discovery nature, 2013)
Indigenous knowledge (IK) can be broadly defined as the knowledge that an indigenous community accumulates over generations of living in a particular environment whose scientific validity is not proven. ITKs could very well provide a panacea in building the technology gap required for the sustenance of the fisheries sector. There are numerous ITKs which is available in fisheries sector whose knowledge components still remain localized and yet to be disseminated across different locations. In this connection a research study was done among 60 randomly selected fisher households in Vypeen island of Ernakulam district using a pre structured interview schedule. The study analyzed the different ITKs available in capture fisheries like identification of fishing ground, time of fishing, weather prediction, fish shoals, determination of depth of water, birds as an indicator of shoals and usage of sinkers and floats. There is innate fear of ITKs disappearing in the future on account of capital intensification in fishing and improved technologies in fish aggregating among the traditional fishermen. These treasure houses of knowledge which are based on the practical experience of indigenous people needs to be documented and validated for the sustainable development of the fisheries sector for the future.